How does mindfulness relate to proenvironmental behavior? The mediating influence of cognitive reappraisal and climate change awareness. (10th July 2022) - Apaolaza, Vanessa; Paredes, Mario R.; Hartmann, Patrick; Barrutia, Jose M.; Echebarria, Carmen
Abstract: Mindfulness has recently been identified as an antecedent of proenvironmental behavior. This study aims to consolidate and expand recent research findings by suggesting that mindfulness is associated with proenvironmental behavior through cognitive reappraisal and climate change awareness. Our findings showed that mindfulness correlated with proenvironmental behavior through both cognitive reappraisal and climate change awareness. Moreover, nature connectedness was found to negatively moderate this relationship: for individuals with greater levels of nature connectedness, the influence of mindfulness on proenvironmental behavior was diminished. Theoretical and practical implications of our findings are discussed. Highlights: Mindfulness relates to pro-environmental behavior through cognitive reappraisal and global climate change perception. Nature connectedness positively relates to global climate change perception. Nature connectedness negatively moderates the mediated relationship of mindfulness with pro-environmental behavior. With higher nature connectedness, mindfulness has a weaker relationship with pro-environmental behavior.